The guide to LGBTQ+ research - Brett, Adam; Lee, Catherine (Emerald Publishing Limited, 2025)
A practical and accessible guide that researchers will draw on time and time again, The Guide to LGBTQ+ Research has at its heart, a commitment to inclusivity. Following the conventions of a doctoral thesis and drawing on the expertise of almost 40 contributors from the field of LGBTQ+ research, this guide offers invaluable support to anyone undertaking research with LGBTQ+ participants. Sharing examples of good practice from those with experience of researching the LGBTQ+ community, each section comprises of vignettes, advice, and case studies from those working in this field. Contributors include a range of experienced academics, early career researchers, research supervisors and doctoral students working in the UK and internationally. Together their vast and diverse voices combine to create a network of support for anyone undertaking LGBTQ+ research. The Guide to LGBTQ+ Research is an essential resource for anyone embarking on master's or doctoral level study. Each chapter aims to build your confidence as a researcher as those with experience and expertise guide you through each stage of your studies. From drawing up your research proposal, right through to publishing from your studies and finding your first academic role, this book will be a vital source of support throughout your research with the LGBTQ+ community.